A quadratic multinomial regression model was established for taste properties of main catechins and amino acid monomers in green tea - RAN Qiansong; LIU Zhongying; LIU Xi; HOU Yanshuang; BAO Fushu; PAN Ke (Shipin yu jixie)
ObjectiveTo study the flavor intensity of green tea after mixing the main flavor monomers.MethodsThree main catechins [epigallocatechin gallate (EGCG), epigallocatechin gallate (GCG), epicatechin gallate (ECG)] and three amino acid monomers (aspartic acid, glutamic acid and theanine) in green tea were studied by electronic tongue detection technique. The evaluation model of green tea taste attribute was constructed by quadratic polynomial regression analysis.ResultsThe intelligent sensory intensity in the matching solution followed the order of umami > astringency > bitter taste. ECG, EGCG interaction with aspartate and glutamic acid had positive effect on bitter taste. Aspartate and glutamic acid had negative effects on the bitterness intensity of theanine. GCG and ECG had a positive effect on astringency, the interaction between catechin and amino acid and glutamic acid with aspartic acid and theanine had a negative effect on astringency. The interaction between glutamic acid, theanine, catechin and amino acid and the interaction between catechin and catechin had a positive effect on umami taste, while the interaction between ECG, theanine, catechin and amino acid, aspartic acid and theanine, glutamic acid and theanine had a negative effect on umami taste. The evaluation model of monomer taste attribute was Y (bitter)=17.033 1+0.927 0X4+0.002 5X32+0.000 2X62+0.001 9X2X5+0.009 3X4X5-0.003 7X4X6-0.000 7X5X6. Y=-32.097 5+0.199 8X2+0.455 3X3+1.222 9X4+0.000 6X22+0.004 4X52-0.000 1X1X6-0.002 6X2X3-0.008 1X3X4-0.017 3X4X5+0.001 4X5X6; Y (fresh)=80.221 8-0.703 7X3+0.555 6X5-0.355 4X6+0.000 7X62-0.001 6X1X2-0.002 7X1X5+0.000 8X1X6+0.007 9X2X3-0.009 7X2X5+0.014 3X3X5-0.002 4X4X6-0.004 8X5X6; The correlation coefficients of the model were all > 0.890 1, and the determination coefficients were all >0.792 2. The reference model taste intensity was 15.17~53.58 in umami, 3.03~15.76 in bitterness, and 5.94~16.52 in astringency.ConclusionThe solution composed of theanine, glutamic acid, aspartic acid, EGCG, GCG and ECG monomers can simulate the flavor intensity of green tea soup to a certain extent, and the highest and lowest intensity of green tea taste properties can be matched according to the three models.